Validity and Reliability of Cognitive Attentional Syndrome-1 Questionnaire - (:unkn) unknown (KOREAN NEUROPSYCHIATRIC ASSOC, 2019)
Objective This study aimed to evaluate the reliability and validity of the Turkish version of Cognitive Attentional Syndrome-1 (CAS-1) questionnaire. Methods 221 participants were included in the study who do not meet any psychiatric diagnosis. Participants were applied SCID I and II and filled CAS-1 scale, Meta-Cognitions Questionnaire-30 (MCQ-30), Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Generalized Anxiety Disorder-7 (GAD-7) Scale, and Penn State Worry Questionnaire (PSWQ). Testing the reliability Cronbach's alpha, item analysis and Item and total score correlation coefficients were applied. For testing structural validity, Confirmatory Factor Analysis was used, and for testing the content validity, the relationship between each item of CAS-1 and MCQ-30, BDI, BAI, GAD-7, PSWQ was examined. Results The correlation reliability coefficients were statistically significant except for using alcohol/drugs as a coping mechanism. Cronbach Alpha reliability coefficient of 16 items was 0.771 whereas, this ratio was 0.772 for the first eight items (CAS) and 0.685 for the last eight items (Metacognitive Beliefs) which showed that the internal consistency of CAS-1 was high. Structural and Content Validity of the scale was significant. Conclusion The Turkish version of the CAS-1 was a reliable and valid measure to evaluate CAS in a Turkish population.
Keywords: Metacognition; Cognitive attentional syndrome; Cognitive attentional syndrome-1; Rumination; Worry; COPING STRATEGIES; ANXIETY; ADAPTATION; DEPRESSION; VALIDATION; RUMINATION; DISORDER; BELIEFS